Navigating the EU AI Act: implications for regulated digital medical products - Aboy, M; Minssen, T; Vayena, E (Nature Research, 2024)
The newly adopted EU AI Act represents a pivotal milestone that heralds a new era of AI regulation across industries. With its broad territorial scope and applicability, this comprehensive legislation establishes stringent requirements for AI systems. In this article, we analyze the AI Act’s impact on digital medical products, such as medical devices: How does the AI Act apply to AI/ML-enabled medical devices? How are they classified? What are the compliance requirements? And, what are the obligations of ‘providers’ of these AI systems? After addressing these foundational questions, we discuss the AI Act’s broader implications for the future of regulated digital medical products.